تنمية القيم الايجابية في الصف الدراسي بمقاربة أسلوبي القصة والتعلم التعاوني - مامنية, سامية (جامعة الوادي - University of Eloued, 2022)
سنتناول في هذا المقال الدور الوظيفي للمدرسة في تنمية القيم الايجابية باعتماد مقاربة أسلوبي القصة والتعلم التعاوني وذلك لما يتميزا به من خصائص تجعل منهما أسلوبين مناسبين لعلاج المشكلات السلوكية والاتجاهات والميولات لدى المتعلمين بما يضمن تعزيز وبناء منظومة قيمية ايجابية ، على أن يتم التركيز على التفاعلات التي تتم وفق هذين الأسلوبين داخل الصف الدراسي. Abstract : In this article, we will discuss the functional role of the school in developing positive values by adopting the approach of the story and cooperative learning methods, because of the characteristics that make them suitable methods for treating behavioral problems and the trends and tendencies of learners in a way that ensures the promotion and building of a positive value system, provided that the focus is on the interactions that take place According to these two methods in the classroom
مقال
Keywords: lمدرسة ; وظيفة ; قيم ايجابية ; قصة ; تعلم تعاوني; school; functional; a story ;positive values ; cooperative learning